BEYOND THE HUMAN CONDITION: DURATION AND VIRTUALITY IN HERACLITUS. (December 2020) - Ellis, Richard
Abstract : Gilles Deleuze's engagement with Heraclitus is long-standing, going back to his early work on Nietzsche, and persisting through the collaborative volumes produced with Félix Guattari in which Heraclitus becomes a key exemplar of their own philosophical method, whereby thought and nature are said to fold into one another in creative configurations. For Deleuze, as before him for Nietzsche, Heraclitus' conception of universal becoming and of the constitutive flows across codes—be they ontological, epistemological, political, or ethical—demands a radical re-evaluation of the place of the human in time, and of the boundaries of subjectivity. Elsewhere, Deleuze states that the very meaning of philosophy is 'to go beyond the human condition' by opening us up to the other durations—inhuman and superhuman—with which, and by which, we are disclosed. A further key interlocutor here is Henri Bergson, whose work on time as duration, with psychological and ontological import, is central to the development of many of Deleuze's philosophical positions, including those subsequently nuanced by his work with Félix Guattari. Before attempting to map the plane of affiliations upon which these thinkers move, it is necessary to begin from Heraclitus' own words on philosophical method and the opposition he draws between the correct, though elusive, practice of νόος ('thought', 'understanding') and the inadequate model of πολυμαθίη ('much learning') adopted by his intellectual predecessors.